Análise numérica da aplicação do controle ativo de arrasto em um modelo automobilístico simples - Valdson Henrique Prado Gonçalves (2019)
Flow control is one of the most used strategies in current vehicle aerodynamics research, especially in relation to the aerodynamic drag reduction of simple automobile models. Numerical analysis of active flow control application on squareback Ahmed body was performed to aim model drag coefficient reduction. At first, unsteady simulations of the Ahmed body without active control were done, with U¥ = 20m/s and Re = 3,6 x 106, based on body length, using SST k-w turbulence model, for mesh validation with CD and Cp experimental data found in the literature. Steady blowing and suction were applied at body rear in two cases, with blowing velocities equal to 1,5U¥ and 2,0U¥. This resulted in a model drag coefficient reduction of 3,5% for Uin j = 1,5U¥, and 4,1% for Uin j = 2,0U¥. The wake characteristics were analyzed for the three cases investigated and modifications in velocity and pressure fields were observed. In addition, the efficiency related with the net power balance was evaluated in both cases of the active control.